Measurement of Low‐Abundance Intracellular mRNA Using Amplified FISH Staining and Image‐Based Flow Cytometry. Issue 1 (1st April 2016) - Henning, Andrea L.; Sampson, Jill N. Best; McFarlin, Brian Keith
Abstract: Recent advances in instrument design and reagent development have enabled the rapid progression in available measurement techniques in the field of flow cytometry. In particular, image‐based flow cytometry extends the analysis capacity found in traditional flow cytometry. Until recently, it was not possible to measure intracellular mRNA in specific phenotypes of cells by flow cytometry. In this protocol, a method of completing simultaneous intracellular measurement of mRNA and protein for PPAR‐gamma in peripheral blood monocytes, which have been exposed in vitro to modified LDL, is described. The process of PPAR‐gamma activation following uptake of modified LDL is believed to play a role in the development of atherogenesis. PPAR‐gamma mRNA measurement was made possible using an amplified FISH technique (PrimeFlow RNA Assay) that allowed for detection of low‐abundant intracellular mRNA expression. This protocol represents a continued effort by the authors' laboratory to establish and validate new techniques to assess the role of the immune system in chronic disease. © 2016 by John Wiley & Sons, Inc.